Unlocking Success in Counseling: How Personality Traits Moderates Its Effectiveness - Alexandro Fortunato; Silvia Andreassi; Costanza Franchini; Gaetano Maria Sciabica; Mara Morelli; Antonio Chirumbolo; Anna Maria Speranza (MDPI AG, 2024)
Psychological distress is widespread among university students, with depression being notably more prevalent compared to the general population. University counseling services are crucial for addressing these mental health challenges, and numerous studies have demonstrated their effectiveness in reducing psychological distress and improving overall well-being. However, there is limited research on what factors predict the success of university counseling. This study aims to evaluate whether counseling improves well-being, specifically by reducing depressive symptoms, and to explore whether personality traits influence counseling outcomes. Participants included 125 Italian university students (64.8% female, mean age = 22.69; SD = 3.04) who utilized counseling services. They completed a socio-demographic questionnaire, the Beck Depression Inventory-II (BDI-II), and the Personality Inventory for DSM-5-TR (PID-5-TR) at three points: immediately after the intake interview (T0), just before the intervention (T1), and after the fourth session (T2). Linear mixed models were used to analyze changes in depression levels, revealing a significant reduction in depressive symptoms from pre- to post-intervention. Among personality traits, only antagonism showed a significant interaction with time. Additionally, higher detachment scores were associated with higher depression levels. These findings emphasize the need for focused attention on students' emotional issues and suggest that personality traits may influence the effectiveness of counseling.